Peran Orang Tua terhadap Pola Asuh dalam Perkembangan Sosial Anak Usia 3-4 Tahun di Kelurahan Kebun Tebeng - Erda, Erda; Agustina, Elsi; Lestari, Intan; Lestari, Maya; Khatoha, Trisqa Laila; Ocktavia, Tyzeka Dwi; Syafri, Fatrica (Asian Journal of Early Childhood and Elementary Education, 2024)
This research aims to describe parental parenting patterns on the social development of children aged 3-4 years in the Kebun Tebeng sub-district, Bengkulu. This research uses a qualitative descriptive research type. The subjects of this research consisted of five parents who had children aged 3-4 years. Data collection techniques through observation, interviews and documentation. The data analysis used in this research is the Miles and Huberman model of qualitative data analysis, which consists of data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the way parents care for children in fostering the social development of children (3-4) years in the Kebun Tebeng Bengkulu sub-district is that parents: 1) guide and pay attention to children, 2). Supervise and give an example to children 3). provide opportunities for children to express their feelings, 4). Respond calmly to the child's behavior.